Electric Circuit Problems with Solutions - Benson, F. A. author. aut Link
X, 258 p.
Keywords: Electrical-engineering and electronic-engineering students have frequently to resolve and simplify quite complex circuits in order to understand them or to obtain numerical results and a sound knowledge of basic circuit theory is therefore essential. The author is very much in favour of tutorials and the solving of problems as a method of education. Experience shows that many engineering students encounter difficulties when they first apply their theoretical knowledge to practical problems. Over a period of about twenty years the author has collected a large number of problems on electric circuits while giving lectures to students attending the first two post-intermediate years of Uni versity engineering courses. The purpose of this book is to present these problems (a total of 365) together with many solutions (some problems, with answers, given at the end of each Chapter, are left as student exercises) in the hope that they will prove of value to other teachers and students. Solutions are separated from the problems so that they will not be seen by accident. The answer is given at the end of each problem, however, for convenience. Parts of the book are based on the author's previous work Electrical Engineering Problems with Solutions which was published in 1954.